PEMBINAAN HUKUM DAN ETIKA DALAM BERKOMUNIKASI PADA REMAJA DI PERUMAHAN BUKIT PERMATA KECAMATAN SAGULUNG KOTA BATAM - Ukas Ukas; Lenny Husna; Kundori Kundori (PUAN INDONESIA, 2023)
Communication is a process of conveying messages from a communicator to a communicant. Communication has elements including communicators, news, media, communicants, and feedback. All of these elements will be interrelated with one another. The rules in the communication process can also be referred to as law and ethics in communication. Sometimes we are a part of the elements of communications that do not understand the law and ethics in communications.  The study of law and ethics in communication is not only related to mass media, such as social media, etc. But in communicating directly there are also laws and ethics in communications. In several cases related to laws and ethics in communication, in these cases affecting mothers and teenagers, due to a lack of understanding and knowledge in communication ethics, sometimes they are trapped in the realm of law which will ensnare them in dealing with applicable laws and regulations. Therefore, guidance related to law and ethics in communicating, both direct and through the media, is significant and must always be carried out. So that a sense of comfort and peace is created and no one is harmed in the communication process. This legal and communication ethics coaching will be doing for five times, as stated in the schedule. Training is carried out simultaneously by the coaching team and members. Method of implementation this community service activity was held three times in meetings involving all youth members and oldsters of the Dianul Jannah mosque at RT 04 RW 17 Perumahan Bukit Permata, Tembesi Village, Sagulung District, Batam City: The Service Team give acknowledgment and direct practice, The Service Team ensured that all members of the mosque understand the material presented also given the time to discuss to be able to understand and apply law and ethics in communicating either directly or through the media.